The Effect of Human Development Index, Domestic Investment (PMDN), and Foreign Direct Investment (PMA) on Labor Absorption in the Sulawesi Region, 2016–2024 - Muhammad Muntazhar Sulaiman; Patta Tope; Kalvin A. Parinding; Laendatu Pembonan; Mohamad Ichwan; Muh. Afief Mubayyin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of the Human Development Index (HDI), Domestic Investment (PMDN), and Foreign Investment (PMA) on labor absorption in the Sulawesi region during 2016–2024, This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) and analyzed using panel data regression. Based on the results of the model selection regression test through the Chow test and the Hausman test, it was obtained that the Fixed Effect Model (FEM) is the most appropriate model. The results of the study show that simultaneously HDI, PMDN, and PMA have a significant effect on labor absorption, with the F Test (Simultaneous) producing a probability value of 0.00000 (< 0.05). Partially, HDI and PMDN have a significant effect. Showing that improving the quality of human resources and domestic investment have an important role in optimizing labor absorption Meanwhile, FDI has no significant effect, indicating that foreign investment has not been able to absorb labor optimally.